A study on the prevalence of retinopathy in newly diagnosed Type 2 diabetes mellitus in a tertiary care center of Tamil Nadu - G, Prakash; M, Kumar Raja; N, Kalaisezhian; T, Yoganandh; Vasanthakumar JA; Nivedhapriya P (Asian Journal of Medical Sciences, 2023)
Background: Type 2 diabetes mellitus (Type 2 DM) is one of the leading risk factors for cardiovascular diseases. Although the awareness of the need for screening and treatment for Type-2 DM is widely prevalent, the awareness of complications arising out of it is not widespread. This article highlights the occurrence of diabetic retinopathy (DR) among newly detected diabetic patients. Aims and Objectives: The aim of the study was to study the prevalence of DR in patients who are diagnosed as having Type 2 diabetes mellitus for the first time. Materials and Methods: The present study involved 501 newly diagnosed Type 2 DM patients. Their history was recorded and the investigations done included haemoglobin (Hb), glycated Hb percent (HbA1c), fasting blood sugar, and post-prandial blood sugar. These patients underwent fundus examination through direct ophthalmoscope and slitlamp examination. Results: Out of the 501 patients in the study, 59.5% (298) had good knowledge about diabetes, but only 3.8% knew about retinopathy. A total of 71.5% of patients did not have periodic eye examination; the most common barrier identified was lack of awareness about the necessity for this (58.5%), 5.6% among the total population had an eye disease. Mild non-proliferative DR (NPDR) was found among 10 females and it was observed in eight males. Moderate NPDR was identified in three males and two females and while no severe cases were reported among the men, two were noted among the women. Conclusion: The study highlights the prevalence of retinopathy in newly diagnosed Type 2 DM population in tertiary care center hospital in Salem district. The study also highlights the importance of detection of Type 2 DM before the occurrence of complications which arise due to diabetes and screening for microvascular complications is necessary at the time of diagnosis of DM and periodically.